Socio-economic factors influencing the voting behavior of people with disabilities in developing nations - Singh, Sukhvir (Journal of Gender Equality Disability Social Inclusion and Children, 2025)
Background: In developing nations, people with disabilities face systemic barriers that impede their full participation in political processes, particularly in voting. This paper explores the intersection of disability and socio-economic factors, analyzing how poverty, education, employment status, and social marginalization affect the voting behavior of disabled individuals. Despite the recognized right to vote, people with disabilities are often excluded from the electoral process due to physical inaccessibility, lack of disability-inclusive policies, and socioeconomic constraints. Methods: Through a sociological lens, this study examines how these individuals' political engagement is shaped by structural inequalities, highlighting the compounded impact of disability and economic disadvantage on voter turnout and political participation. Drawing on case studies from low-resource settings. Findings: This paper demonstrates that people with disabilities in developing countries face multiple barriers to exercising their right to vote. These barriers include accessible polling stations, voter education, and legal frameworks protecting political rights. These structural inequalities directly impact the voting behavior and levels of political participation of people with disabilities, particularly in resource-limited settings. Conclusion: This study emphasizes the importance of inclusive policy reforms to eliminate the specific barriers that people with disabilities face in the electoral process. This requires accessibility to polling stations, voter education targeted to disability groups, and legal protection of their political rights. Novelty/Originality of this article: The novelty/originality of this article lies in its sociological analysis of how disability intersects with poverty, education, and employment to shape political participation, emphasizing structural barriers and advocating for inclusive electoral policies in developing nations.